Crime Occurrence and Hotel Operating Performance: An Empirical Investigation in Ibadan Municipality, Nigeria - Oladehinde, Gbenga John; OLADELE , Adeola Francisca; ADENIYI , Lateef Adeleke; OLADEJI , Peter Bolaji; OGUNGBE , Mayowa Adedapo (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
The incidence of crime and the effects it has on the operating performance of hotels has received a lot of attention, but it is hardly researched in African contexts. The study aims to examine the effect of crime on the hotel operating performance in Ibadan, Nigeria. Questionnaires were used to collect the data for the study. A systematic sampling technique was used in the selection of hotel staff for this study. Mean, correlation, ANOVA, and Stepwise regression were used in the analysis and interpretation of data. The study discovered that theft was the most occurring crime in hotel settings. The use of Stepwise regression shows that guest satisfaction, guest loyalty, patronage level of guests, employee turnover, revenue generation, achievement of organization goals, and sales of hotel products were the significant parameters of hotel performance that were affected while wastage of organizational resources was not. The study showed that there is a correlation between crime and hotel operating performance. It was concluded based on the findings that the incidence of crime strongly affected the operating performance of the hotel business in the study area. This study addressed both theoretical implications that provide support for the framework (routine activity theory and hot spot theory) and practical implications that offer suggestions for effective crime prevention strategies.